Comparative Accuracy of Static Virtual Versus Conventional Articulation in Dental Arches: A Systematic Review and Meta-Analysis - M. Rathod, Asha; S Mistry, Gaurang; Singh, Rajeev; M. De Souza, Mishal; V. Chitnis, Ankita; J. Shukla, Mansi (Journal of Neonatal Surgery, 2025)
The evolution of digital workflows in prosthodontics has introduced static virtual articulation as a modern alternative to conventional mechanical articulators for simulating occlusal relationships. This systematic review and meta-analysis aimed to compare the accuracy, efficiency, and clinical applicability of static virtual and conventional articulation methods in dentate and partially edentulous patients. Comprehensive electronic searches were conducted across PubMed, Cochrane Library, and Google Scholar, following PRISMA 2020 guidelines and Cochrane standards. Studies were included if they compared static virtual and conventional articulators based on articulation accuracy, time efficiency, reproducibility, patient satisfaction, or cost-effectiveness. Risk of bias was assessed using appropriate tools based on study design, including AMSTAR 2 and ROBINS-I. Meta-analysis was performed where appropriate using a random-effects model. Results indicated that static virtual articulators demonstrated statistically significant improvements in accuracy and efficiency, along with benefits such as reduced chairside time and improved patient experience. However, limitations remain, particularly in capturing dynamic mandibular movements, which may affect outcomes in complex occlusal cases. The review concludes that static virtual articulation is a clinically viable and precise alternative for routine prosthodontic use, though further high-quality research is needed for broader application in advanced rehabilitative contexts